2017
DOI: 10.1007/s40751-017-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Primary Programming and Mathematics: Some Findings of Design Research in England

Abstract: In this paper we present the background, aims and methodology of the ScratchMaths (SM) project, which has designed curriculum materials and professional development (PD) to support mathematical learning through programming for pupils aged between 9 and 11 years. The project was framed by the particular context of computing in the English education system alongside the long history of research and development in programming and mathematics. In this paper, we present a Bframework for action^(diSessa and Cobb, Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 24 publications
3
84
0
16
Order By: Relevance
“…The research reported within this paper is a part of a broader project, ScratchMaths (SM), which aims to explore connections between developing computational and mathematical thinking in the upper primary age pupils 4 in England [17,18]. In the project we have iteratively designed detailed curriculum materials for computing lessons in years 5 and 6, which are currently being trialled in 50+ primary schools across the country.…”
Section: Procedural Abstraction Within Scratchmathsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research reported within this paper is a part of a broader project, ScratchMaths (SM), which aims to explore connections between developing computational and mathematical thinking in the upper primary age pupils 4 in England [17,18]. In the project we have iteratively designed detailed curriculum materials for computing lessons in years 5 and 6, which are currently being trialled in 50+ primary schools across the country.…”
Section: Procedural Abstraction Within Scratchmathsmentioning
confidence: 99%
“…2 -right). Within our SM pedagogical framework [17] we encourage 5 In Scratch a stack of blocks snapped together, a piece of program 6 The topmost block to start a script, e.g. when this sprite clicked hat block 7 In the context of SM Module 1, patterns of actions are procedural representations of the corresponding visual patterns 557 pupils to follow the procedure: (i) build a script, debug and use it, (ii) give it a name, i.e.…”
Section: Sm Pedagogic Strategy For Definitionsmentioning
confidence: 99%
“…His background for designing the curriculum materials was an interest in maths education and coding in general and Scratch in particular. Despite his lack of training, the tasks in Programming in Maths in point of fact align with tasks previously documented to support the learning of mathematics through coding (Benton, Hoyles, Kalas, & Noss, ). Therefore, they form an appropriate outset for investigating how Scratch coding affects interest development.…”
Section: Methodsmentioning
confidence: 73%
“…Scratch is a visual blocksbased language that allows children to build scripts (programs) through snapping together different coloured blocks (commands), thus circumventing to a large extent the syntax errors that caused issues in many earlier programming languages for children such as Logo (Resnick et al, 2009). 6 The overall pedagogic approach in the SM project comprises five unordered constructs-Explore, Explain, Exchange, Envisage, and bridgE (the "5Es"), which have structured the whole classroom approach to the different activities in the SM curriculum (see Benton et al, 2017). 6 The overall pedagogic approach in the SM project comprises five unordered constructs-Explore, Explain, Exchange, Envisage, and bridgE (the "5Es"), which have structured the whole classroom approach to the different activities in the SM curriculum (see Benton et al, 2017).…”
Section: The Role Of Scratchmentioning
confidence: 99%
“…Conceptual challenges are of course still evident, and in the absence of syntax issues, debugging can mainly focus on the algorithmic level (Foerster, 2016). 6 The overall pedagogic approach in the SM project comprises five unordered constructs-Explore, Explain, Exchange, Envisage, and bridgE (the "5Es"), which have structured the whole classroom approach to the different activities in the SM curriculum (see Benton et al, 2017). The approach was also shaped by constructionism, that is, to seek to foster learning as building knowledge structures by learners actively engaging together in "constructing a public entity" (Papert, 1980).…”
Section: The Role Of Scratchmentioning
confidence: 99%